2017
DOI: 10.1016/j.neuron.2017.03.036
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic Regulation of Sucrose Seeking during Unexpected Reward Omission

Abstract: SUMMARY The paraventricular nucleus of the thalamus (PVT) is thought to regulate behavioral responses under emotionally arousing conditions. Reward-associated cues activate PVT neurons, however, the specific PVT efferents regulating reward-seeking remain elusive. Using a cued sucrose-seeking task, we manipulated PVT activity under two emotionally distinct conditions: 1) when reward was available during the cue as expected, or 2) when reward was unexpectedly omitted during the cue. Pharmacological inactivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
204
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 152 publications
(226 citation statements)
references
References 105 publications
(143 reference statements)
20
204
2
Order By: Relevance
“…It is not clear whether we would have seen similar effects of stimulating other excitatory glutamatergic inputs into the AcbSh although recent studies support a role for multiple inputs, including the prefrontal cortex and the thalamus, in reward seeking and consumption (Britt et al, 2012; Do-Monte et al, 2017; Prado et al, 2016; Selleck and Baldo, 2017; Stuber et al, 2011). For example, Britt et al found that mice will respond for activation of prefrontal, BLA, or hippocampual accumbal inputs (Britt et al, 2012).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…It is not clear whether we would have seen similar effects of stimulating other excitatory glutamatergic inputs into the AcbSh although recent studies support a role for multiple inputs, including the prefrontal cortex and the thalamus, in reward seeking and consumption (Britt et al, 2012; Do-Monte et al, 2017; Prado et al, 2016; Selleck and Baldo, 2017; Stuber et al, 2011). For example, Britt et al found that mice will respond for activation of prefrontal, BLA, or hippocampual accumbal inputs (Britt et al, 2012).…”
Section: Discussionmentioning
confidence: 85%
“…The prefrontal cortex has been suggested to be critical for behavior selection and for switching between appetitive and consummatory behavior (c.f.,(Selleck and Baldo, 2017). Additionally, activation of inputs from the paraventricular nucleus of the thalamus during instrumental nosepoking for sucrose decreases nosepoke responding, yet did not reduce ad libitum sucrose consumption (Do-Monte et al, 2017). Notably, our study used a stimulation train of five seconds, while others (c.f., Britt et al, 2012; Do-Monte et al, 2017) utilize stimulation trains ranging from one to fifteen seconds, which may drive AcbSh units more powerfully than typically observed; while there is utility in probing potential functionality using current optogenetics approaches, studies that attempt to mimic natural activity patterns using brief and low intensity stimulation are a future goal.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the PVT-NAc pathway is involved in the acquisition of cocaine self-administration (Neumann et al 2016), as well as mediating symptoms during drug withdrawal (Zhu et al 2016). Recently, however, it was shown that pharmacological inactivation of the anterior, but not the posterior, PVT increases sucrose-seeking behavior upon reward omission, and that this behavior is specifically mediated by aPVT projections to the NAc shell (Do-Monte et al 2017). In contrast, differences in food-cue-induced neuronal activity between STs and GTs seems to be restricted to cells projecting from the posterior PVT (pPVT) to the “shore” (area bordering the core/shell) of the nucleus accumbens (Haight et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, however, we targeted a specific nucleus that had been identified as a key player in these Pavlovian learning processes (Flagel et al 2011a, Haight and Flagel 2014, Haight et al 2015, Yager et al 2015, Haight et al 2017), to determine whether the same nucleus acts to encode the incentive value of a cue that was previously paired with operant drug delivery. While it is known that the neural circuitry mediating Pavlovian conditioning can differ from that mediating instrumental behavior (Ostlund et al 2007, Yin et al 2008, Wassum et al 2011), the paraventricular nucleus of the thalamus appears to be involved in both (Hamlin et al 2009, James et al 2010, Browning et al 2014, Haight et al 2015, Matzeu et al 2015, Neumann et al 2016, Do-Monte et al 2017, Matzeu et al 2017, Otis et al 2017). The current findings support a role for this nucleus in the attribution of incentive value to reward cues and suggest that, in a subset of individuals, the PVT acts to suppress the learned incentive value of such cues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation